Integrated characterization of an organic-rich caprock shale, Svalbard, Arctic Norway - Senger, K.; Mulrooney, M.; Braathen, A.; Ogata, K.; Olaussen, S. (European Association of Geoscientists and Engineers, EAGE, 2016)
Both thermogenic and biogenic gas were encountered during scientific drilling on Svalbard, Arctic Norway. The thermogenic gas has been encountered in an interval at 650-703 m depth, spanning both the lower part of the caprock, an organic-rich shale unit with subordinate siltstone intervals, and the upper part of the siliciclastic reservoir targeted for CO2 storage. Both water injection tests and gas flow tests were conducted to establish the formation injectivity and production capability of this interval. In this contribution, we investigate the organic rich shale interval in detail, integrating well data with direct observations on outcrop analogues, to present a conceptual model of the reservoir-cap rock interface.